3D Vanadium Oxide Inverse Opal Growth by Electrodeposition. Issue 14 (9th October 2015) - Armstrong, Eileen; O'Sullivan, Maria; O'Connell, John; Holmes, Justin D.; O'Dwyer, Colm
Abstract : Three-dimensional vanadium pentoxide (V2 O5 ) material architectures in the form of inverse opals (IOs) were fabricated using a simple electrodeposition process into artificial opal templates on stainless steel foil using an aqueous solution of VOSO4 .χH2 O with added ethanol. The direct deposition of V2 O5 IOs was compared with V2 O5 planar electrodeposition and confirms a similar progressive nucleation and growth mechanism. An in-depth examination of the chemical and morphological nature of the IO material was performed using X-ray crystallography, X-ray photoelectron spectroscopy, Raman scattering and scanning/transmission electron microscopy. Electrodeposition is demonstrated to be a function of the interstitial void fraction of the artificial opal and ionic diffusivity that leads to high quality, phase pure V2 O5 inverse opals is not adversely affected by diffusion pathway tortuosity. Methods to alleviate electrodeposited overlayer formation on the artificial opal templates for the fabrication of the porous 3D structures are also demonstrated. Such a 3D material is ideally suited as a cathode for lithium ion batteries, electrochromic devices, sensors and for applications requiring high surface area electrochemically active metal oxides.